(untitled) (World Conference on Social Sciences, Law and Public Policy, 2026)
This paper examines the grounds for the civil liability of a legal entity for intellectual property infringements directly committed by its employee. Drawing on the legislation of the Republic of Uzbekistan and comparative legal scholarship, it distinguishes the direct liability of a legal entity from vicarious liability for an employee’s conduct. The paper proposes criteria for determining whether an infringement is sufficiently connected with the employee’s duties, analyses the impact of corporate IP compliance on the employer’s liability, and considers the limits of recourse claims against the employee.